PWE-319 The relationship with body composition of ccr7-positive cells in colorectal cancer. (22nd June 2015) - Malietzis, G; Lee, GH; Bernardo, D; Knight, S; Moorghen, M; Al-Hassi, HO; Jenkins, JT
Abstract : Introduction: Emerging data support the link between systemic inflammatory response (IR) and body composition alterations in cancer patients but limited information exists on how the local IR to the tumour is associated to these changes. Regulation of the local IR is largely achieved through chemokine synthesis from the tumour microenvironment such as C-Chemokine-Receptor-7 (CCR7). In the present study, we determined the expression of CCR7 in primary colorectal cancer (CRC) and also correlated the expression of CCR7 with the patients' clinical and pathological parameters (including their body composition derived from computerised tomography (CT) analysis) to explore the relationship between body composition and tumour immunology in CRC. Method: A study of paraffin-embedded tissue specimens was carried out in 116 patients with non-metastatic CRC. CCR7 expression was determined by immunohistochemistry. Analysis of computer tomography scans was used to calculate BC parameters. The relationship between CCR7 expression and other clinicopathological parameters was assessed using nonparametric statistics. Results: The median tumour infiltrating CCR7+ cell density was 15.85% (Inter Quartile Range (IQR) 10.02–21.83%) in the tumour stroma, and 7.17% (IQR 3.90–12.37%) at the tumour margin. CCR7+ cell density of the two areas correlated positively (Spearman r = 0.77; p < 00.001). We divided the cases into high and low CCR7+ groups according to the median value of CCR7 + cell density. High CCR7+ cell density at both the tumour centre and the margin was significantly associated with older age, higher tumour stage, lymph node metastasis and the presence of myosteatosis. High CCR7+ cell density at the tumour margin was also significantly associated with female sex and the presence of lymphovascular invasion. There was no significant association between CCR7+ cell density either at the margin or within an intra-tumoural location with BMI, site of tumour, grade of differentiation, myopenia or visceral adiposity. Conclusion: We found that a high density of tumour-infiltrating CCR7+ cells was significantly associated with age, histological invasion, higher tumour stage, lymph node metastasis and myosteatosis that are adverse prognostic factors in CRC. These findings may therefore suggest a model whereby the stimulus for the local immune cell response is not only induced by the tumour but also influenced by host-related factors. We have now identified that myosteatosis is also related to an adverse local inflammatory response as measured by a high CCR7 density. To our knowledge these findings are novel and may support the hypothesis that host LIR may influence the development and persistence of myosteatosis. Disclosure of interest: None Declared.